The Effect of Giving Education with Power Point Leaflet Media and Isi Piningku Video on Increasing Knowledge of Balanced Nutrition in Students at SMP Negeri 7 Nabire Province Central Papua - Ithe Kogoya; Nur Susan Iriyanti Ibrahim; Gandhi Pratama (International Journal of Medicine and Health, 2024)
Nutritional problems in school children include malnutrition and overnutrition due to lack of education, so there needs to be education on the contents of my plate related to balanced nutrition. One of the program efforts that can be implemented by the government so that people live healthy and well-nourished is by providing education on the "Isi Piringku" movement. An effective way to increase knowledge of balanced nutrition so that students can apply a healthy diet. Objective: This study aims to analyze the effectiveness of education on the media Power Point, Leaflets, Videos on the Contents of My Plate on Increasing Knowledge of Balanced Nutrition at SMP Negeri 7 Nabire. Method: Using a Pre Experiment Design research design with a One Group Pretest-Posttest Design approach. The sample in this study amounted to 54 students using the types of media Power Point, Leaflets, Videos which were divided into 3 experimental groups. Results: there is an effect of providing education on the Contents of My Plate on increasing knowledge of Balanced Nutrition through Power Point, Leaflet, Video media through a TestPaired Samples Testone of them is Video media (P = 0.000) on Students at SMPN 7. Conclusion: that educational media assistance Power Point, Leaflet, Video, can influence to increase knowledge of Students at SMP Negeri 7 Nabire. Suggestion: For further research can continue the research by developing Power Point media, Leaflet, Video and other educational media.